Analysis of Parking Characteristics in Rest Area Km 726 B in Planning Parking Space Needs at Rest Area Facilities STA 19+600 Manjungan Klaten Village Solo-Yogyakarta-Nyia Kulon Progo Toll Road Section I Package 1.1 Solo Klaten (STA 0+000 – 22+300) - Yayuk Sri Rahayu; Nunung Widyaningsih (Jurnal Syntax Transformation, 2024)
The problem of traffic jams continues to increase, the government is designing an alternative road connecting Surakarta to Yogyakarta. The increasing volume of vehicles on the Solo - Yogyakarta toll road makes accidents prone due to driver negligence. To reduce the risk of accidents and relieve fatigue after traveling, one of the policies taken is to build rest areas and facilities. The method used in the research is a direct survey to obtain primary data in the form of incoming and outgoing vehicle data, the number of existing parked vehicles, facilities in rest areas and secondary data in the form of daily traffic on the Solo - Yogyakarta toll road obtained from PT. JMM. Based on the condition of the existing rest area, it is necessary to analyze the parking facilities to get an idea of ​​parking capacity and parking space requirements. The guideline used in the research is "Guidelines for Planning and Operation of Parking Facilities for the Directorate of City Transport Traffic System Development 1998", as well as references related to parking analysis. The conclusion of the analysis results is that the parking space needed for the Solo-Yogyakarta toll road in the 2024 planning year is 271 SRP, the volume of incoming vehicles is 2751, the accumulation is 206 vehicles, the parking index is 75.99%, the turnover is 10.15, and in 2033 there are parking spaces. What is needed is a capacity of 541 SRP, a volume of incoming vehicles of 5495, an accumulation of 411 vehicles, a parking index of 76.07%, and a turnover of 10.16.